EVALUATION OF THE CYTOCHROME P450 INHIBITORY EFFECT OF THYME OLEORESIN FROM THYMUS VULGARIS L. - AN IN VITRO STUDYEVALUATION OF THE CYTOCHROME P450 INHIBITORY EFFECT OF THYME OLEORESIN FROM THYMUS VULGARIS L. - AN IN VITRO STUDY - Anitha, Roy; R, Adeline Persia; Lakshmi, Thangavelu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to evaluate the effect of thyme oleoresin on cytochrome P450 (CYP3A4) enzyme. Materials and Methods: The different concentrations of thyme oleoresin (5–100 μg/ml) were examined for its inhibitory property toward cytochrome P450 isoform (CYP3A4). Thyme oleoresin, potassium phosphate buffer, CYP450 reagent, and substrate 7-Benzyloxy-4-trifluoromethylcoumarin were added to a 96-well plate. The mixtures were preincubated for 20 min at room temperature. The fluorescent intensities of the products were measured by PerkinElmer Enspire fluorescence reader using an excitation and emission wavelength of 405 nm and 460 nm, respectively. Values were expressed as mean ± standard error mean (n=3). IC50 was calculated by plotting concentrations of thyme against the corresponding percent inhibition. Results: All the tested concentrations of thyme showed inhibitory effect against CYP3A4 in a dose-dependent manner. At 5 μg/ml, it showed a percentage inhibition of 1.82±0.61, whereas 100 μg/ml showed 66.05±0.16. The IC50 value of thyme for CYP3A4 inhibitory activity was found to be 39.14 μg/ml. Conclusion: This study prove the inhibitory effect of thyme oleoresin on cytochrome P450. The inhibitory effect of thyme oleoresin indicates the possibilities of herb-drug interaction if this extract is co-administered with prescribed drugs that are metabolized by CYP3A4.